PENGARUH BERMAIN PERAN (ROLE PLAYING) MAKRO TERHADAP PENINGKATAN KOSAKATA BAHASA INDONESIA ANAK TAMAN KANAK-KANAK - Amilah Fitriani (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2021)
Language development in early childhood in general is still a lot that has not developed optimally, especially in kindergarten children. During the Q&A activities, it is often difficult for children to express vocabulary, children still have difficulty understanding the vocabulary spoken by the teacher. In the role playing method, children can learn to express language and can acquire new vocabulary, especially Indonesian vocabulary. The interaction and communication that occurs in the role playing method as a stimulus for children in developing their language vocabulary. The selection of the right theme in role playing activities for children is adjusted to the level of needs and closeness of early childhood. Therefore, teachers as educators must be creative, innovative and cooperative in making learning methods to help the development of students optimally.